Molecular imprisonment: Host response to guest location, orientation, and dynamics in clathrates of Dianin's compound - Lee, J.; Sobolev, A.; Turner, M.; Fuller, Rebecca; Iversen, B.; Koutsantonis, G.; Spackman, M. (American Chemical Society, 2014)
Single crystal X-ray diffraction data measured at 100 K for Dianin's compound (DC) and 18 of its clathrates formed with a wide range of guest molecules provide considerable insight into the way the host adjusts to accommodate guest molecules. Detailed information is also obtained regarding the location, orientation, and dynamics of the guests in the host cavity. Although all unit cells are closely similar in size, the host undergoes significant change in response to the imprisonment of its various guests. Enclathration typically results in a larger cell and cavity volume, but for the small molecules methanol, ethanol, and nitromethane the host actually shrinks significantly around the guests in the cavity. In most clathrates, there is evidence of close contacts between atoms in the guest and the phenol -OH group and/or ring of the DC host. The series of clathrates formed by benzene, toluene, and the halobenzenes show the orientation of the benzene ring to be progressively modifed by the increasing size of the substituent atom or group on the ring in a systematic manner that reflects functional group contributions to van der Waals volumes. © 2014 American Chemical Society.